A new body-fitted immersed volume method for the modeling of ductile fracture at the microscale: Analysis of void clusters and stress state effects on coalescence. (October 2015) - Shakoor, Modesar; Bernacki, Marc; Bouchard, Pierre-Olivier
Highlights: Heterogeneous materials are modeled with a new body-fitted immersed volume method. Thanks to remeshing, new interfaces are captured on-the-fly during the simulation. Void coalescence is addressed and modeled directly at the microscale. Finite element analysis is performed until and after the onset of void coalescence. Numerical experiments include random void arrangements and various stress states. Abstract: In this work, a new finite element framework is developed and applied to the study and modeling of ductile fracture mechanisms at the microscale. More particularly, a body-fitted meshing and remeshing methodology is introduced and applications to void coalescence are investigated. Though most studies focus on periodic arrangements of voids, it was proven in experiments as in simulations that random void clusters have a major influence on void growth and coalescence. With the method proposed in this paper, various void arrangements can be addressed and their effect on void growth and coalescence can be studied at large plastic strain and various stress states.